2018
DOI: 10.1155/2018/1681056
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Intradialytic Hypertension and Metabolic Disorders in End Stage Renal Disease

Abstract: Background Intradialytic hypertension was associated with a high mortality risk. We examined the relationship between intradialytic hypertension and metabolic disorders in hemodialysis treatment patients. Methods We studied 76 patients in online hemodiafiltration. Dialysis adequacy was defined by Kt/V for urea. Normalized protein catabolic rate (nPCR), as a marker of protein intake, was calculated. Sodium removal was determined as percent sodium removal. Metabolic acidosis was determined by serum bicarbonate l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 42 publications
3
9
1
Order By: Relevance
“…In our study, the average age of patients was 45.51 years (Table 2). This result is different from those found by other authors; 50.69 -13.89 years [5] and 38.0 -5.9 [13], but much lower than that found in Greece 70.2 -14.3 years [14]. We found a statistically significant link (p-0.044) between age and the occurrence of DHBP.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, the average age of patients was 45.51 years (Table 2). This result is different from those found by other authors; 50.69 -13.89 years [5] and 38.0 -5.9 [13], but much lower than that found in Greece 70.2 -14.3 years [14]. We found a statistically significant link (p-0.044) between age and the occurrence of DHBP.…”
Section: Discussioncontrasting
confidence: 99%
“…Until further studies determine the pathophysiologic mechanism, we cannot conclude whether the presence of vascular calcification is a risk factor for intradialytic hypotension or if it is an independent condition that occurs in distressed patients with ESRD on hemodialysis. Likewise, some studies have established that patients with intradialytic hypertension had stiff arteries assessed by pulse wave velocity, 29,30 but the relationship of either arterial stiffness or vascular calcification with intradialytic hypertension remains unclear. In summary, this study concludes that calcified vessels may be unconnected to intradialytic BP abnormalities, so further research is essential to clarify the vascular factors that cause a considerable BP drop or rise over the course of dialysis treatment.…”
Section: Figmentioning
confidence: 99%
“…In a subsequent cross-sectional study, patients with IDH exhibited higher carotid-femoral PWV and augmentation index (AIx) compared with patients without IDH. 17 Finally, in a previous study of our group, we demonstrated that patients with IDH had significantly higher pre-dialysis PWV and AIx(75), together with a negligible reduction in AIx(75) during dialysis compared with individuals without IDH. 18 As patients with IDH display a different brachial BP trajectory during the intra-and interdialytic period and a higher cardiovascular risk than those without the phenomenon, and since ambulatory PWV in haemodialysis displays much stronger associations with mortality than office PWV, we designed a study to examine ambulatory central BP and arterial stiffness parameters and trajectories in patients with and without IDH during a standard 48-h period covering the dialysis session and the interdialytic interval.…”
Section: Introductionmentioning
confidence: 49%